Strokes by Barbare Jorjadze for a literary portrait - Nikoleishvili, Avtandil (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2021)
Assessing the role of Barbare Jorjadze (1833-1895) in the history of Georgian literature, the fact that she was an active participant in the struggle between the generations in the 60s and 70s of the XIX century and uncompromisingly defended the conservative position of the older generation became more interesting than her literary heritage. Views. It should also be emphasized that B. Jorjadze was the first professional female writer in Georgia, who made creative work the main direction of her life. she was even such a popular figure at the time that the authors of many letters and poems about their author, published in periodicals at the time, praised her work, especially the performances based on her plays. Unfortunately, this creative popularity of Barbara Jorjadze turned out to be so short that „the author herself lived longer than his work“ (Vakhtang Kotetishvili). The interest of today›s readers in the work of Barbare Jorjadze is essentially determined by the fact that through her we are given even more opportunities to know the reality of Georgia in the time of the writer. Barbare Jorjadze›s writing abilities were most evident in her prose texts. The two main factors that made such an assessment of his work created in this genre became the following: The narrative drama of the stories narrated in them and the linguistic controversy, which is significantly different from the poetic texts, the obvious distancing of the narration from the old Georgian grammatical forms and the closeness to the spoken speech. Of Barbare Jorjadze›s prose works, the novelistic texts about the invasion of the armed gangs of the North Caucasus Mountain tribes in Kakheti and the decrease of the local population in Kakheti are especially important for today›s readers. In the writer›s prose narratives, this tragic event is first and foremost connected with Shamil›s name. Barbare Jorjadze›s creative recognition was also related to the success she achieved with the performances based on her plays. In particular, her dramatic works were very popular in the writer›s life and were firmly established in the repertoire of Georgian theaters of that time. One of the main factors determining the interest of today›s readers in the creative heritage of Barbare Jorjadze should be considered the fact that the writer often appeared in the role of an active defender of women›s rights. From this point of view, her artistic-publicist texts, as well as her active practical participation in public activities are extremely interesting.